Thermal strain is greater in the late afternoon than morning during exercise in the gym without airflow and air conditioning on a clear summer day - Otani, Hidenori; Goto, Takayuki; Kobayashi, Yuki; Goto, Heita; Shirato, Minayuki; Hosokawa, Yuri; Tokizawa, Ken; Kaya, Mitsuharu (Frontiers in Sports and Active Living, 2023)
Introduction: There are no reports examining the time-of-day effect on team training sessions in the gym without airflow and air conditioning on thermal strain in the summer heat. We investigated this effect during badminton training sessions on a clear summer day. Methods: Nine male high school badminton players (Mean±SD; age 17.1±0.6 y, height 171±4 cm, body mass 59±7 kg) completed two 2.5-h badminton training sessions in the gym without airflow and air conditioning. The training sessions were started at 0900 h (AM) and 1600 h (PM) on separate days in August. Skin temperatures (chest, triceps, thigh, calf), infrared tympanic temperature, heart rate, thermal sensation and rating of perceived exertion were recorded at rest and at regular intervals during the sessions. Results: Indoor and outdoor environmental heat stress progressively increased in AM and decreased in PM during the sessions. Ambient temperature (AM 30.1±0.9°C; PM 33.2±1.0°C: P<0.001) and wet-bulb globe temperature (AM 28.1±0.5°C; PM 30.0±0.9°C: P=0.001) during the sessions in the gym were higher in PM than AM. Mean skin temperature (AM 34.2±1.0°C; PM 34.7±0.7°C: P<0.001), infrared tympanic temperature (AM 37.8±0.5°C; PM 38.1±0.4°C: P=0.001) and thermal sensation (AM 2.7±1.4; PM 3.3±1.0: P<0.001) during the sessions were higher in PM than AM. Body heat storage (AM 159±30 W·m−2; PM 193±30 W·m−2: P<0.05) was greater in PM than AM. There were no time-of-day differences in the average heart rate (AM 75±4% age-predicted maximal heart rate; PM 76±5 age-predicted maximal heart rate: P=0.534), body mass loss (AM 0.6±0.3 kg; PM 0.8±0.2°C: P=0.079), the volume of water ingested (AM 1.5±0.1 L; PM 1.6±0.3 L: P=0.447) and rating of perceived exertion (AM 16±2; PM 16±3: P=0.281). Conclusions: This study indicates greater thermal strain in PM trial than in AM trial during team training sessions in the gym without airflow and air conditioning on a clear summer day. Therefore, athletes and coaches of indoor sports should perceive that athletes may be exposed to a greater risk for thermal strain in the late afternoon from 1600 h than in the morning from 0900 h during the sessions in the gym under these conditions.